Estudo da ação tripanomicida do extrato bruto de Mandevilla velutina em camundongos infectados com Trypanosotna cruzi - Silva, Regildo Márcio Gonçalves da (1999)
Chagas disease is one of the most important parasitic infections in several regions of Latin America, including Brazil, due to its high incidence, prevalence and socio-economic repercussions that this endemic causes to countries. Despite efforts, a very small number of trypanomycin drugs have been indicated for the specific treatment of the disease, all with side effects that limit use. In the Uberlândia region, there are popular reports that the rhizome extract of Mandevilla velutina is indicated for patients with this disease. This work was developed in order to investigate the action of this extract on the parasitemia and mortality of mice infected with 5x104 blood forms of the T. cruzi Y strain. The extract was obtained by macerating fragments of the rhizome in 15% cereal alcohol, which was lyophilized (EBL) and resuspended in distilled water. The EBL administered to the mice, orally, presented a low toxicity in the organism of these animals. When EBL was administered in increasing doses (up to 200mg / kg) in mice infected with T. cruzi, a reduction in parasitemia and an increase in survival were observed, which were dose dependent. The previous treatment of the animals, with a dose of 200mg / kg, proved to be effective in reducing parasitemia, being more efficient when the treatment was carried out 24 hours before infection. When infected animals were treated with two daily doses of EBL (71.5 and 143 mg / kg) for 30 days and compared with animals treated with Benzonidazole (two daily doses of 50 mg / kg), it was found that EBL is more effective than Benzonidazole in the doses administered. To investigate the possible involvement of the NO System in the mechanism of action of the EBL, infected animals were treated with EBL and NOS inhibitor (NOARG or L-NAME) where an attenuation of the effects of the EBL was observed. When measuring NO2 and NO3 in the serum of normal animals and treated with EBL, there was a significant increase in NO2 and NO3 concentrations. When comparing parasitemia and serum NO3 levels of infected animals treated and not treated with EBL, it was found that the untreated animals showed higher values ​​of parasitemia and NO3, between the 8th and 14th day post-infection. The trypanomicidal action promoted by the EBL, was also tested in vitro in the blood containing T. cruzi, incubated with EBL (24 and 48 hours), resulting in the reduction of the trypomastigote count. In the evaluation of the genotoxic potential of the EBL, the results suggest that the EBL has protective effects on the formation of 'onucleated erythrocytes. In the phytochemical screening, the presence of several auímic classes was verified, including the tannins and the terpenoids, which may present anti-parasitic activity. This work suggests that the crude M. velutina extract has a component (s) capable of acting on the parasitemia of mice infected with T. cruzi, significantly reducing the number of parasites during infection, and this reduction may be correlated with the Nitric Oxide System.